The Effect of Diprydamole on Flow-Mediated Dilatation in Patients with Slow Coronary Flow - Ermis, Necip; Akturk, Erdal; Sincer, Isa; Ozdemir, Ramazan; Cehreli, Sengul (Annals of Medical Research, 2021)
None